Diagnosis and Planning in the Management of Musculoskeletal Tumors - A Review (Faridpur Medical College Journal, 2017)
The prognosis of patients with musculoskeletal tumors has improved markedly because of the advent of new chemotherapeutic drugs and regimens and as a result of advances in imaging and surgical techniques. Limb-salvage operations can currently be performed with better outcomes, while in the past; limbs with tumors were treated only with amputation. Accurate preoperative surgical staging of musculoskeletal tumors is currently possible because imaging techniques provide prognostic information and aid clinicians in choosing the most appropriate treatment option for the patient. The aim of this article is to outline the presentation, imaging, and staging of the primary and metastatic bone and soft tissue tumors. Some of the image-guided interventions for these tumors are also presented.Faridpur Med. Coll. J. Jul 2016;11(2): 81-85